2015
DOI: 10.1002/2015ms000503
|View full text |Cite
|
Sign up to set email alerts
|

Attributing the behavior of low‐level clouds in large‐scale models to subgrid‐scale parameterizations

Abstract: This study explores ways of establishing the characteristic behavior of boundary layer schemes in representing subtropical marine low-level clouds in climate models. To this purpose, parameterization schemes are studied in both isolated and interactive mode with the larger-scale circulation. Results of the EUCLIPSE/GASS intercomparison study for Single-Column Models (SCM) on low-level cloud transitions are compared to General Circulation Model (GCM) results from the CFMIP-2 project at selected grid points in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…For example, Dal Gesso et al () compare SCM simulations of stratocumulus to results with their host GCM, making use of a phase‐space approach. Alternatively Neggers () make use of the fingerprints of models in κ ‐TCC space to compare SCM and GCM simulations at selected gridpoints in the Eastern Pacific, reporting that GCM behavior can to some extent be attributed to subgrid physics as apparent in SCM simulations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dal Gesso et al () compare SCM simulations of stratocumulus to results with their host GCM, making use of a phase‐space approach. Alternatively Neggers () make use of the fingerprints of models in κ ‐TCC space to compare SCM and GCM simulations at selected gridpoints in the Eastern Pacific, reporting that GCM behavior can to some extent be attributed to subgrid physics as apparent in SCM simulations.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a study on the representation of the SCT in large-scale models by Neggers (2015), it is found that SCMs favor a breakup of stratocumulus for inversion conditions that are unique to each individual model. The presence of such modes may be indicative of a local hydrological cycle that is distinctively different among the models.…”
Section: Discussionmentioning
confidence: 99%
“…The time evolution of the subcloud mixed-layer height h can be expressed in terms of the mass budget equation (Neggers et al 2006),…”
Section: A Evolution Of the Subcloud-layer Heightmentioning
confidence: 99%
“…Most errors can be rapidly detected and also rapidly diagnosed with debugging tools which work on single processors. An SCM provides rapid feedback on model and code changes in minutes using modest computer resources, compared to running the full GCM, but is representative of GCM results (Neggers, ).…”
Section: Introductionmentioning
confidence: 99%